2017
DOI: 10.1016/j.dib.2017.09.074
|View full text |Cite
|
Sign up to set email alerts
|

FTIR and GC–MS spectral datasets of wax from Pinus roxburghii Sarg. needles biomass

Abstract: The study has been carried out to investigate the chemical composition and type of linkages present in wax obtained from Pinus roxburghii Sarg. needles biomass. The spectroscopic techniques viz. FT-IR and GC–MS were employed to obtain spectral datasets. The results were analysed to identify major structural components constituting wax in native state. The spectral recordings were carried out at three different stages which include native wax, hydrolysed fatty acids and their corresponding methyl esters. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“… The dataset can be used for educational purposes, drug synthesis and multidisciplinary research. Similar data articles can be found in [1] , [2] . …”
supporting
confidence: 68%
See 1 more Smart Citation
“… The dataset can be used for educational purposes, drug synthesis and multidisciplinary research. Similar data articles can be found in [1] , [2] . …”
supporting
confidence: 68%
“…Crude extracts were used for qualitative phytochemical analysis) FTIR (Range – 4000-650 cm −1 , Resolution – 8 cm −1 , Microlab PC software with ATR sampling unit) GCMS (Column - 30 mm × 0.25 mm ID × 0.25 μm film, Carrier gas - Helium, flow - 1.0 ml/min, electron ionization - 70 Ev, Software - Masshunter) Experimental features Phytochemical analysis of carbohydrates, tannins, saponins, flavonoids, alkaloids, anthocyanins, betacyanins, quinones, glycosides, cardiac glycosides, terpenoids, triterpenoids, phenols, coumarins, steroids, acids, FTIR scan of functional groups and GCMS scan of bioactive constituents. Data source location Ota, Nigeria Data accessibility Data included in this article Related research article [1] P. Dubey, P. Sharma, V. Kumar, FTIR and GC–MS spectral datasets of wax from Pinus roxburghii Sarg . needles biomass, Data Brief.…”
mentioning
confidence: 99%
“…, but its disadvantage is it's deteriorating effects on wooden objects such as darkening/ yellowing, it can be infested with microorganisms [30], and is an unstable material that deteriorates due to the occurrence of an oxidation process when exposed to UV [31] [32]. By comparing the functional groups of the second sample taken from the object with the standard functional groups of bees wax [27][33] [34] [35], it was confirmed that bees wax was used to treat the panel in the past. Its disadvantages have been discussed in the experimental part of this paper.…”
Section: Fourier-transform Infrared Spectrometry (Ftir)mentioning
confidence: 99%
“…The spectral band at 1471 cm −1 and 1463 cm −1 stands for symmetric angular stretching or bending vibration of CH 2 [ 50 ]. Two continuous bands at 728 cm −1 and 718 cm −1 correspond to the in-plane CH 2 deformation [ 51 ]. A distinct peak at 1732 cm −1 corresponds to the stretching vibration of –C=O present in ester.…”
Section: Resultsmentioning
confidence: 99%